Bronchodilators, Antibiotics, and Oral Corticosteroids Use in Primary Care for Children With Cough - Sankaran Krishnan MD, MPH; Vicki Ianotti MD; John Welter MD; Meighan Maye Gallagher BA; Tatiana Ndjatou MD; Allen J. Dozor MD (SAGE Publishing, 2019)
Real-world management decisions for acute cough in children in primary care practice are not well understood. This study is an analysis of 560 encounters for children with cough, 19 days to 18 years of age, seen in a predominantly suburban academic pediatric practice, over 1 year. Past history, cough duration, and cough characteristics significantly affected treatment decisions. Children with cough frequently had a history of preterm birth, allergies, asthma, and neurological conditions. Most common therapies were bronchodilators, antibiotics, and oral corticosteroids. Children prescribed antibiotics were older, more likely to have a wet or productive cough, history of sinusitis, pneumonia or dysphagia, and longer cough duration. Children prescribed oral corticosteroids were younger, less likely to be wet or productive and more likely to have history of asthma or dysphagia. Children prescribed bronchodilators were more likely to have fever, nasal congestion, and wheezing and history of previous asthma, pneumonia, or dysphagia.